A qualitative study of abortion professionals’ perspectives on doula support - Martha Paynter; Anja McLeod; Clare Heggie; Wendy V. Norman (PLoS ONE, 2025)
Objective(s) Doulas provide non-clinical support to people in pregnancy, labour and delivery, and, increasingly, to abortion-seekers. Even in contexts of decriminalization and proactive policy efforts to enhance access, barriers to abortion persist, especially for patients experiencing intersecting forms of oppression. Abortion doulas may play a role in improving access. This qualitative study explores the potential involvement of doulas in abortion services from the perspective of abortion health professionals and clinic administrative staff. Study design This is a qualitative study. Participants were asked about experiences with doulas and potential doula contributions to abortion services. Data were analysed using thematic analysis. Results We conducted two focus groups and five individual interviews for a total of 18 participants. Participants perceived challenges to incorporating doulas formally into the abortion clinic setting, although they saw the possibility for doula support before and after receipt of abortion services. Conclusion(s) Our findings suggest abortion health professionals and clinic administrative staff perceive roles for doulas largely external to the clinical setting, to provide support for equity-deserving groups. They have concerns about the presence of doulas in the clinic due to policies against support people and because of the unregulated, unstandardized nature of doula practice. Implications This qualitative study addresses the potential for integration of doulas with abortion care from the perspective of abortion clinic health professional and administrative staff. To our knowledge, this is the first study on this topic in Canada.